IGZO‐TFT technology for large‐screen 8K display - Hara, Yoshihito; Kikuchi, Tetsuo; Kitagawa, Hideki; Morinaga, Junichi; Ohgami, Hiroyuki; Imai, Hajime; Daitoh, Tohru; Matsuo, Takuya (Journal of the Society for Information Display, 2018)
We succeeded in G8 factory for mass production of Indium–Gallium–Zink–Oxide thin‐film transistor (IGZO‐TFT) for the first time in the world. The initial TFT process was an etching stop‐type TFT, but now, we are mass producing channel etching‐type TFTs. And, its application range is smartphones, tablets, PCs, monitors, TV, and so on. In particular, because of recent demands for high‐resolution and narrow frame, our IGZO display has been advanced in technology development with gate driver in panel. In this paper, we report development combining low resistance technology and the latest IGZO‐TFT (IGZO5) for large‐screen 8K display. We developed the fifth generation IGZO‐TFT. Its mobility was 15 cm2/Vs, and high reliability was confirmed. In addition, we developed a low resistance technology. We report the development combining low resistance technology and the latest IGZO‐TFT for large‐screen display of 8K 120 Hz with single data‐line structure.